Oil Spinner Machine to Improve the Quality of UMKM Chips Products in the Community of Food and Beverage Processed Association (IMO) of Sumatera Utara - Nasution, Dian Morfi; Bukit, Ferry Rahmat A.; Hasugian, Ivo Andika; Hasibuan, Novrida Harpah (ABDIMAS TALENTA: Jurnal Pengabdian Kepada Masyarakat, 2021)
Home industry is now increasingly in demand by the community as a form of "Usaha Mikro Kecil Menengah (UMKM) " that have simple concepts and promising results. Many business ideas and opportunities that can be realized into a home industry business, one of which is food processing. UMKM have a major contribution to the rolling of the economy of a country, not only as a seed that generates the growth of big business but also provides certain services for the community which for large businesses are considered to be less cost-efficient. The IMO (Ikatan Makanan Minuman Olahan) of Sumatera Utara is one of the communities that oversees several UMKM entrepreneurs spread across Sumatera Utara. Types of snack products that are quite popular are cassava chips, banana chips, and crackers. Almost all chips processing is done by frying. A problem that is often experienced is the level of oil in chips that are still included in the packaging. This is due to the process of draining the oil which is still done manually. It takes a touch of technology to replace the manual process into a mechanical system that is with a spinner or known as a cooking oil drainer. The target and output of this activity is to achieve an increase in the quality of chips production under the IMO through the use of appropriate technology, namely a simple and low-cost oil-spinning machine.